68Ga-DOTATATE and 18F-FDG PET/CT for the Management of Esthesioneuroblastoma of the Sphenoclival Region. (August 2020) - Dadgar, Habibollah; Norouzbeigi, Nasim; Ahmadzadehfar, Hojjat; Assadi, Majid
Abstract : Abstract: We present a 48-year-old woman with an olfactory neuroblastoma who was referred for accurate staging using PET/CT. The 68 Ga-DOTATATE PET/CT showed a 51 × 32-mm mass with an SUVmax of 7.59 in the sphenoidal sinuses, whereas radiotracer uptake on 18 F-FDG PET/CT was similar to that of brain tissue. 68 Ga-DOTATATE PET/CT might be especially useful in regions with difficult tumor visualization resulting from high background, such as brain tissue. The results of this case may suggest that somatostatin receptor imaging in patients with esthesioneuroblastoma may facilitate the potential application of radiotheranostic agents for the treatment of this aggressive subtype of tumors.